نقد متون السُّنة النبوية في تأصيلات الإمام الشافعي قراءة لعلامات الوصل بين أصول الفقه وأصول الحديث - نجم الدين قادر الزنكي (International Institute of Islamic Thought, 2011)
تبحث الدراسة منهج الشافعي في نقد متون السُّنة بياناً وصفياً تحليلياً. وقد خلُصَتْ إلى أن السُّنة عند الشافعي تَثبُت بنفسها لا بغيرها، من عمل الراوي، أو أهل المدينة، أو قياس الأصول. ويُختبَر الحديثُ عنده بثقة الراوي وعدالته وعقله لما يَحْمِل. فإن كان لا يُدرِك ما يَروي وهو غير ناقل للحديث بلفظه؛ سقطت روايته، وهانتْ، ولم تُقبل. This study defines Shafi'i's methodology in the assessment of the content (matn) of Hadith, adopting a descriptive and analytical methodology. It concludes that, according to Shafi'i, an established Sunnah is evident and does not need any external evidence to verify, e.g. practices of the narrators, people of Madinah and the so-called 'regulative analogy'. However, the credibility of narrators and their explicitness of inference are the measure taken for this course of examination. Therefore, a Hadith cannot be authoritative if the narrator lacks legal understanding and proves to be unprofessional in narration.